Synthesis of ZnO nanorod for immunosensor application - Doan, Vu Y; Vuong, Pham Hung; Lan, Hoang; Tam, Phuong Dinh (Vietnam Journal of Chemistry, 2016)
This paper reported a facile method to synthesize ZnO nanorods for immunosensor application. The ZnO nanorods were synthesized by hydrothermal reaction. Synthesis time affecting on morphology of nanorods was also studied. The immobilization of anti-rotavirus onto ZnO nanorod-deposited sensor was performed via absorption method. The electrochemical responses of the immunosensor were studied by cyclic voltammetry (C-V) method with [Fe(CN)6]3−/4− as redox probe. A linear decreased response in C-V for cell of rotavirus concentration was found in the range of 7.8×105 CFU/mL to 7.8×108 CFU/mL. The detection limit of the immunosensor was 7.8×105 CFU/mL. The results indicated application of ZnO nanorod sensor for label-free real-time detection of a wide dynamics range of biological species.